As plataformas digitais na produção da cidade contemporânea: uma análise urbanística do Airbnb em cidades brasileiras - Pedro Henrique Cícero Ferreira (2021)
Founded under the 2008 financial and real estate crisis, the short-term rental digital platform, Airbnb, made it possible to intermediate local agents in monetizing their idle properties and travellers in search for a more authentic and low-cost tourism. After gaining global presence in the accommodation market, the platform increasingly distanced from the collaborative practices. In such context, Airbnb configured itself as a digital space where dominant real estate players produce housing as a commodity, concentrating most part of the profits generated and removing properties from the long-term rental market. As a technology enterprise, Airbnb is not subject to most of the regulations concerning tourism and housing, hence reproducing its activities within the scope of informality, a situation that may cause a series of socio-spatial contradictions. Scientific research from several knowledge fields dedicated their efforts to studying such impacts, mainly concerning north-american and european cities, which constructs a narrative of Airbnb through the perspective of those epistemological and geographical places. This research contributes to the scientific production around Airbnb, departing from the Brazilian territorial reality. Therefore, proposes to question how the urbanization processes operated by the referred platform interact with others historically and geographically accumulated, focusing on the socio-spatial transformations and the housing accessibility conditions. Aiming to construct a conceptual framework for analysis, this research appeals to authors from different disciplinary fields (political economy, geography, technology, urbanism, among others), approaching concepts such as platform capitalism, sharing economy, neoliberalism and platform urbanism. Other references of this research are the case studies, by various authors, about Airbnb spatial distribution in cities all over the world. Tied to such references, the empirical analysis elaborated deals with the spatial process of Airbnb in Curitiba, São Paulo, Belo Horizonte and other small cities, such as Bombinhas, Caldas Novas e Ubatuba. With these research procedures, it's expected to improve the understanding of how Airbnb, and other platforms in general, act in the production of brazilian cities spaces in contemporaneity, a context where digital technology increasingly becomes a central factor in mobilizing urbanization processes.